A rice single cell transcriptomic atlas defines the developmental trajectories of rice floret and inflorescence meristems. Issue 2 (24th February 2022) - Zong, Jie; Wang, Li; Zhu, Lu; Bian, Lianle; Zhang, Bo; Chen, Xiaofei; Huang, Guoqiang; Zhang, Xuelian; Fan, Junyi; Cao, Liming; Coupland, George; Liang, Wanqi; et al.
Summary: Rice inflorescence development determines yield and relies on the activity of axillary meristems (AMs); however, high‐resolution analysis of its early development is lacking. Here, we have used high‐throughput single‐cell RNA sequencing to profile 37 571 rice inflorescence cells and constructed a genome‐scale gene expression resource covering the inflorescence‐to‐floret transition during early reproductive development. The differentiation trajectories of florets and AMs were reconstructed, and discrete cell types and groups of regulators in the highly heterogeneous young inflorescence were identified and then validated by in situ hybridization and with fluorescent marker lines. Our data demonstrate that a WOX transcription factor, DWARF TILLER1, regulates flower meristem activity, and provide evidence for the role of auxin in rice inflorescence branching by exploring the expression and biological role of the auxin importer OsAUX1. Our comprehensive transcriptomic atlas of early rice inflorescence development, supported by genetic evidence, provides single‐cell‐level insights into AM differentiation and floret development.